RELEVANSI BIROKRASI WEBERIAN TERHADAP PENGUATAN TATA KELOLA PEMERINTAHAN DI INDONESIA - Natasya Eva Tania; Dela Puspita; Annisa Kurnia Sari; Aulia Neza Agustin Febriana; Fitria Novita Sari (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
This study aims to analyze the concept of Weberian bureaucracy and assess its relevance to improving and strengthening governance in Indonesia. The research focuses on answering how Weberian principles are understood within the context of public administration and the extent to which these principles can support a professional, accountable, and effective government system. The study employs a library research method with a descriptive qualitative approach. Data were obtained from Max Weber’s works, public administration literature, scholarly articles on bureaucracy, and policy documents related to Indonesia’s Bureaucratic Reform agenda. Data collection was carried out through systematic literature review by reading, noting, and categorizing key information. The dara were the analyzed using content analysis to interpret central ideas concerning legal-rational authority, hierarchical structures, impersonal rules, and bureaucratic profesionalism. The findings indicate that Weberian principles remain relevant as a foundational framework for establisging a structured and accountable bureaucracy. However, Indonesia’s bureaucratic system continues to face challenges such a rigid hierarchical arrangements, slow technological adaption, and the persistance of patronage culture. Therefore, Weberian principles need to be integrated with modern governance innovations to enhance bureaucratic performance and improve the quality of public services.